Thực trạng quản lí hoạt động dạy học môn Toán tại các trường trung học cơ sở huyện Hóc Môn, Thành phố Hồ Chí Minh - Cao , Thị Thanh Xuân; Trần , Thị Hồng Thanh (Tạp chí Giáo dục, 2024)
In high schools, Mathematics has a very important role and meaning, contributing to the formation and development of key qualities, general abilities and mathematical competences for students. The quality of teaching Mathematics at the secondary school level in Hoc Mon district, Ho Chi Minh City is not as expected due to many reasons, including many limitations in the management of this activity. This study points out some advantages and limitations in the management of Mathematics teaching activities at secondary schools in Hoc Mon district, Ho Chi Minh City. The research results will be an important practical basis to help principals of these schools take appropriate management measures in the future.